Sclerochoroidal calcification as an incidental finding during oncological staging of a patient with parotid malignancy: A case report - Lassandro, Nicola Vito; Danieli, Luca; Nicolai, Michele; Pirani, Vittorio; Pelliccioni, Paolo; Mariotti, Cesare (European journal of ophthalmology, 2022)
Incidental finding of mass lesion in the choroid represents a very challenging situation for the ophthalmologist. We describe a case of an incidental, computed tomography (CT)-hyperintense, choroidal lesion in a patient with parotid malignancy and renal failure, and how multimodal imaging helped us reaching the correct diagnosis. A 63-year-old man with parotid gland malignancy was brought to our attention because preoperative staging CT showed a hyperintense choroidal lesion of the right eye. Fundus examination showed a yellow elevated lesion near the superior temporal branch retinal artery. Enhanced depth imaging optical coherence tomography (EDI-OCT), A- and B-scan ultrasonography, and Indocyanine Green Angiography (ICGA) allowed us to exclude a malignant lesion and to diagnose a sclerochoroidal calcification. Multimodal imaging can guide the clinician to choose the appropriate therapeutic approach even in case of uncommon conditions like sclerochoroidal calcification.